'Digitising health protection schemes in Ghana': An enquiry into factors associated with the use of a mobile phone-based health insurance contribution payment system among tertiary students - Anthony Kwame Morgan; Daniel Katey; Moses Asori; Stephen Uwumbordo Nachibi; Ellen Onyina; Theophilus Quartey; Justin Cobbold; Modesta Akipase Aziire (SAGE Publishing, 2024)
In 2018, Ghana's National Health Insurance Scheme (NHIS) introduced a mobile money payment system for membership renewal and premium payments to enhance enrolment and retention rates. However, the adoption of such innovations depends on various factors, including personal traits and public perceptions. This study aims to explore the determinants of NHIS membership renewal and premium payment via the mobile renewal system. Conducted at Kwame Nkrumah University of Science and Technology (KNUST) in Kumasi, Ghana, the study used a survey design to gather data from 951 KNUST students. Employing logistic regression analysis, the study identified key factors influencing the use of the NHIS mobile renewal service. The findings revealed that individuals aged 19-21, 25-27 or above 27, without mobile money accounts, and those with no history of online purchases were less likely to adopt the mobile renewal system ( P  < .05). Conversely, those perceiving the system as useful and easy to use were more likely to utilise it for NHIS membership renewal ( P  < .05). In conclusion, policymakers should prioritise system quality, accessibility, perceived ease of use, and usefulness to facilitate the adoption and usage of the NHIS mobile payment system. These findings contribute valuable insights for enhancing the effectiveness of health insurance innovations.